Republic of Cameroon : Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (2016)
Cameroon is a lower-middle income country with social indicators and levels of poverty which are below those for comparator countries. Large and rising inequalities between north and south, inefficiencies in public resource allocation and an adverse business environment explain this. While insecurity due to Boko Haram activities and rapidly rising public debt constrain efforts at poverty reduction, there exists a huge potential for economic growth and poverty reduction. This potential remains mostly untapped. Realizing it will require far reaching reforms, particularly with respect to the business environment and public financial management, and require politically courage to accomplish. The remainder of this document explores how to achieve the twin goals of ending poverty and improving shared prosperity by 2030 in a sustainable manner. The document identifies a limited number of binding constraints which would need to be lifted to achieve the poverty objective. The next four chapters present background material to chapter six, which presents binding constraints to poverty reduction. The micro-foundations to poverty reduction are discussed in chapters two and three. Chapter two discusses poverty, equity and vulnerability. Chapter three discusses human capital and its role in poverty reduction. Chapter four considers poverty reduction from a macro-economic perspective. It discusses opportunities for growth and economic transformation as well as the status of various cross-cutting economic services. Chapter five, considers governance, fragility and the institutional environment. Binding constraints to sustainable poverty reduction are identified in chapter six.